1990
DOI: 10.1111/j.1365-3083.1990.tb02791.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole Cholera Toxin and B Subunit Act Synergistically as an Adjuvant for the Mucosal Immune Response of Mice to Keyhole Limpet Haemocyanin

Abstract: Cholera toxin (CT) is a potent stimulator of IgA responses when administered orally and has been shown to promote IgA responses to a second protein such as keyhole limpet haemocyanin (KLH) if this is fed simultaneously. In this paper we show that whilst feeding 5 mg KLH with either 0.5 micrograms CT or 10 micrograms B subunit fails to stimulate a mucosal IgA response to KLH, feeding 0.5 microgram CT and 10 micrograms B subunit together with 5 mg KLH produces a local IgA anti-KLH response as great as that produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Previous studies demonstrated that it is advantageous to increase the immunogenicity of vaccine antigens by coadministration of an appropriate adjuvant. Cholera toxin (CT) is a well-known mucosal adjuvant, stimulating antigenspecific secretory IgA and systemic IgG antibody responses to unrelated antigens when coadministered via the oral, nasal, or genital route (14,32,47). The CT holotoxin consists of two subunits: a toxigenic A subunit (CTA), which activates the adenylate cyclase system, and a pentameric B subunit (CTB), which is responsible for CT binding to GM1 gangliosides on the cell membrane.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that it is advantageous to increase the immunogenicity of vaccine antigens by coadministration of an appropriate adjuvant. Cholera toxin (CT) is a well-known mucosal adjuvant, stimulating antigenspecific secretory IgA and systemic IgG antibody responses to unrelated antigens when coadministered via the oral, nasal, or genital route (14,32,47). The CT holotoxin consists of two subunits: a toxigenic A subunit (CTA), which activates the adenylate cyclase system, and a pentameric B subunit (CTB), which is responsible for CT binding to GM1 gangliosides on the cell membrane.…”
mentioning
confidence: 99%
“…epithelial layer that may produce inhibitory cytokines (9). Some investigators have suggested that the adjuvant mechanism of CT is linked to the ability to ADP-ribosylate and to stimulate cyclic AMP (cAMP) formation (23), and that the adjuvant activity of natural CTB may be due to the presence of the trace amounts of CTA that are frequently present in CTB preparations obtained from CT holotoxin (6,20,33,38). We purified a large amount of recombinant cholera toxin B subunit (rCTB) secreted by Bacillus brevis carrying pNU212-CTB (14,43), and it showed powerful adjuvant properties for biologicals without the holotoxin (15,16).…”
mentioning
confidence: 99%
“…A possibility exists that CT exerts a bidirectional influence on the antigen presentation. One action is an inhibition by CTA through an increase in cAMP, and the other is an enhancement by CTB alone or with a trace amount of CT [6,7,[31][32][33]. In some cases, CTB alone might act as a co-stimulator on the surface of APC [16].…”
Section: Discussionmentioning
confidence: 99%